Etnomatematika: Eksplorasi Transformasi Geometri Tenun Suku Sasak Sukarara - Sutarto Sutarto; Intan Dwi Hastuti; Sri Supiyati (Jurnal Elemen, 2021)
Mathematics is considered as a subject that still far from reality and culture. Historically, mathematics has closely related to everyday life, including culture in Lombok West Nusa Tenggara. This culture can explore mathematical concepts to bring mathematics closer to reality and people's perceptions and cultural aspects as the basis for learning mathematics in schools. Therefore, this study explores the elements of geometry transformation in the weaving of the Sasak Sukarara tribe of Central Lombok from an ethnomathematics point of view. This research is qualitative research embracing an ethnographic approach. Data collection methods were carried out through observation and interviews with cultural leaders and native weavers from Sukarara, Central Lombok. The data analysis technique in this study used content analysis and triangulation techniques. The content analysis technique provides detailed data dealing with the weaving culture and habits of the research subjects carried out at the research location. The data source triangulation technique was carried out by comprehensively exploring the relationship between the mathematical knowledge system and the weaving motif culture and looking at the mathematical conceptions that exist in the Sukarara weaving motif. This study showed that in the motifs of wayang, subahnale, keker, four stars, and alang/lumbung, the concepts of reflection and translation could be used as learning resources for geometry transformation materials.